Promising Antifungal Targets Against Candida albicans Based on Ion Homeostasis - Li, Yiman; Sun, Licui; Lu, Chunyan; Gong, Ying; Li, Min; Sun, Shujuan (Frontiers in Cellular and Infection Microbiology, 2018)
In recent decades, invasive fungal infections have been increasing significantly, contributing to high incidence and mortality in immunosuppressed patients. Candida albicans (C. albicans) is the most prevalent opportunistic fungal pathogen in humans that can cause severe and often fatal bloodstream infections. Current antifungal agents have several limitations, including that only a small number of classes of antifungals are available, certain of which have severe toxicity and high cost. Moreover, the emergence of drug resistance is a new limitation of successful patient outcomes. Therefore, the development of antifungals with novel targets is an essential strategy for the efficient management of C. albicans infections. It is widely recognized that ion homeostasis is crucial for all living cells. Many studies have identified that ion-signaling and transduction networks are central to fungal survival by regulating gene expression, morphological transition, host invasion, stress response and drug resistance. Dysregulation of ion homeostasis rapidly mediates cell death, forming the mechanistic basis of a growing number of compounds that elicit antifungal activity. Most of the potent antifungals have been widely used in the clinic, and certain of them have low toxicity, meaning that they may be expected to be used as antifungal drugs in the future. Hence, we briefly summarize the homeostasis regulation of several important ions, potential antifungal targets based on these ion-signaling networks and antifungal compounds based on the disruption of ion homeostasis. This summary will help in designing effective drugs and identifying new targets for combating fungal diseases.